Comparative study of the resolution efficiency of HPLC and HPTLC-densitometric methods for the analysis of mebeverine hydrochloride and chlordiazepoxide in their binary mixture - Michael, Adel Magdy; Fayez, Yasmin Mohamed; Nessim, Christine Kamal; Lotfy, Hayam Mahmoud (European Journal of Chemistry, 2016)
Accurate, rapid, and selective reversed phase HPLC and HPTLC-densitometric methods with UV detection have been developed and validated for simultaneous determination of a binary mixture of mebeverine hydrochloride (MVH) and chlordiazepoxide (CDZ) in their Co-formulation. For the HPLC method, ACE-126-2546 AQ C-18 column, (250×4.6 mm i.d., 5 μm particle size) in isocratic mode, with mobile phase containing 25 mM ammonium acetate buffer: acetonitrile in the ratio of (60:40, v:v), pH adjusted to 3±0.2 by using hydrochloric acid, the flow rate of 1.0 mL/min and detection was performed at 260 nm. The retention times were 7.23±0.01 and 3.85±0.01 min for MVH and CDZ, respectively. For the HPTLC-densitometric method, the separation was performed using stationary phase pre-coated silica gel 60F254 and mobile phase ethyl acetate: methanol (8:4, v:v) were used and scanned at 222 nm with Camag TLC scanner controlled by Wincats Software. The Rf values were 0.26±0.02 and 0.73±0.01 for MVH and CDZ, respectively. The linearity graphs for MVH and CDZ, respectively, were found to be linear over 1-50 μg/mL and 0.5-40.0 μg/mL with mean percentage recoveries 100.14±0.354 and 99.70±0.764 for HPLC method and 0.5-30.0 μg/band and 1-14 μg/band with mean percentage recoveries 100.29±0.665 and 99.68±0.987 for HPTLC-densitometric method. A comparative study of different analytical validation parameters such as accuracy, precision, specificity, robustness was conducted. The obtained results were statistically compared with those of the official methods; using student t-test, F-test, and one way ANOVA, showing no significant difference with respect to accuracy and precision.